CURRENT ISSUES OF HEALTH AND WELLNESS TOURISM BASED ON POPULATION HEALTH PRESERVATION IN EASTERN KAZAKHSTAN - Shynar SHYNGYSBAEVA; Abdimazhit SAIPOV; Ardak ALDASHEVA; Gulshat ATAEVA; Nursaule MAKHANOVA; Erim CANTÜRK (Geo Journal of Tourism and Geosites, 2023)
Research is aimed at elucidating the salient challenges impeding the maturation of the health and wellness tourism cluster within the Eastern Kazakhstan region. The inquiry encompasses findings from a customer survey conducted within the Eastern Kazakhstan Region's sanatorium resort visitors in Katon-Karagay District in 2022-2023. Significant attention is devoted to the natural-ecological, economic-infrastructure, and socio-cultural components constituting the tourist cluster are expounded upon. Quantitative analysis revealed therapeutic mineral baths for targeted activities and massage for complementary activities to be the most fitting activities in the region’s sanatoriums. Satisfaction rates detected 98% for the quality of medical services, 95% for the professionalism of medical personnel, 90% for medical procedures, 88.9% for entertainment programs, and 68.9% for children's activities. Critical challenges in medical and wellness tourism include insufficient accommodations for SPA and wellness, VIP segment tourists, and health-oriented tourist activities, including catering to children. The nation witnesses a promising landscape for the "Katon-Karagay" sanatorium-resort cluster, underscoring the imperative of establishing a public-private partnership and highlighting the need for a public-private partnership.